Chronic widespread pain after motor vehicle collision typically occurs through immediate development and nonrecovery: results of an emergency department-based cohort study. Issue 2 (February 2016) - Hu, JunMei; Bortsov, Andrey V.; Ballina, Lauren; Orrey, Danielle C.; Swor, Robert A.; Peak, David; Jones, Jeffrey; Rathlev, Niels; Lee, David C.; Domeier, Robert; Hendry, Phyllis; Parry, Blair A.; et al.
Abstract : Abstract: Motor vehicle collision (MVC) can trigger chronic widespread pain (CWP) development in vulnerable individuals. Whether such CWP typically develops through the evolution of pain from regional to widespread or through the early development of widespread pain with nonrecovery is currently unknown. We evaluated the trajectory of CWP development (American College of Rheumatology criteria) among 948 European–American individuals who presented to the emergency department (ED) for care in the early aftermath of MVC. Pain extent was assessed in the ED and 6 weeks, 6 months, and 1 year after MVC on 100%, 91%, 89%, and 91% of participants, respectively. Individuals who reported prior CWP at the time of ED evaluation (n = 53) were excluded. Trajectory modeling identified a 2-group solution as optimal, with the Bayes Factor value (138) indicating strong model selection. Linear solution plots supported a nonrecovery model. Although the number of body regions with pain in the non-CWP group steadily declined, the number of body regions with pain in the CWP trajectory group (192/895, 22%) remained relatively constant over time. These data support the hypothesis that individuals who develop CWP after MVC develop widespread pain in the early aftermath of MVC, which does not remit. Abstract : Our results support the hypothesis that individuals who develop chronic widespread pain after motor vehicle collision develop widespread pain in the early aftermath with nonrecovery.